The behaviour of fibre-reinforced composites subjected to a soft impact-loading: An experimental and numerical study. (April 2020) - Liu, Haibao; Liu, Jun; Kaboglu, Cihan; Zhou, Jin; Kong, Xiangshao; Blackman, Bamber R.K.; Kinloch, Anthony J.; Dear, John P.
Highlights: This paper presents experimental and numerical studies on the behaviour of composite laminates subject to impact loading by soft projectiles. Gas-gun experiments are performed to study woven carbon-fibre reinforced poly (ether-ether ketone) (CF/PEEK) composites and woven carbon-fibre reinforced epoxy (CF/epoxy) composite specimens subjected to an impact by soft-gelatine projectiles. High-speed cameras are employed to capture the projectile deformation and a three-dimensional (3D) Digital Image Correlation (DIC) system is used to record the deformation of the impacted composite specimens. A Finite Element (FE) model is developed to simulate the impact by a soft projectile on the composite specimens and validated using the extracted experimental results extracted from the gas-gun experiments. Abstract: The present paper presents experimental and numerical studies on the behaviour of composite laminates subject to impact loading by soft projectiles to represent the impact of a small bird or hail-stone. In this research, gas-gun experiments are performed to study woven carbon-fibre reinforced poly (ether-ether ketone) (CF/PEEK) composites subjected to an impact by soft-gelatine projectiles. In addition, woven carbon-fibre reinforced epoxy (CF/epoxy) composite specimens are also evaluated using gelatine projectiles to investigate the effect of the matrix system on the impact response of the composites. A high-speed camera is employed to capture the deformation of the projectiles and a three-dimensional (3D) Digital Image Correlation (DIC) system is used to record the deformation of the impacted composite specimens. A Finite Element (FE) model is developed to simulate the impact by a soft projectile on the composite specimens. Good agreement is shown between the predictions from using the FE model and the experimental results.